Performance Analysis on Integrated System of Mechanical Refrigeration and Thermosyphon - Zhang Hainan; Shao Shuangquan; Tian Changqing (Zhileng xuebao)
Cutting down the energy consumption of air conditioners in data centers is an urgent need for realizing emission control targets. Thermosyphon (heat pipe) free cooling is one of the effective methods. To solve the need of mechanical refrigeration in hot seasons and improve the energy-saving rate of thermosyphon free cooling, a new type integrated system of mechanical refrigeration and thermosyphon is proposed. A three-fluid heat exchanger is used to connect the mechanical refrigeration loop and thermosyphon loop, achieving the simultaneous work of refrigeration and thermosyphon and avoiding the risk brought by solenoid valve. The performance of the system is tested in an enthalpy difference lab. The results show that the best filling ratio is 100%. The three working modes all have sufficient cooling capacity. The EER of thermosyphon mode reaches 20.8 when the indoor and outdoor temperature difference is 20 ℃. The simulation results of a data center in Jinan show that the new system saves 40% energy of a year compared to traditional ones and have great application potential.